The effect of big-five personality traits on psychological empowerment / Amir Masoud Tabatabaei Yazdi - Amir Masoud, Tabatabaei Yazdi (2017)
The conceptualization of psychological empowerment, which operationalized empowerment from individual perspective, has made it feasible to identify individual characteristics that boost employees’ feeling of empowerment. By testing some personality traits as antecedents of psychological empowerment, few empirical studies suggested that some individuals are more empowered. Despite the importance of identifying empowered individuals, only few personality traits had been tested as antecedent of psychological empowerment, and most of those personality traits were limited to the individuals’ perception of self-worth. Therefore, a thorough investigation for assessing a wide range of personality traits as antecedents of psychological empowerment was required in order to properly answer the question: who is empowered? To fill this void, this research tested big-five personality traits (i.e. one of the best measures of personality which covers a wide range of human personality) as antecedents of psychological empowerment to clarify which personality trait enhances employees’ feeling of empowerment. For the development of hypothesis, this study used a similar mechanism to Spreitzer’s (1995). In other words, for justifying the relationship between each of the big-five personality traits and psychological empowerment, the theoretical link between each of those personality traits and at least one of psychological empowerment’s dimensions was identified. All the big-five personality traits were found to be theoretically related to at least one of the psychological empowerment’s dimension. After finalizing the translated measurement instrument using the pilot study (with sample of 44 service-workers), research hypotheses were tested using both the regression analysis and structural equation modelling on the sample of 372 front-line employees working in organizations within the service sector in Malaysia. The research findings indicated that service-workers high in extraversion, openness, conscientiousness, and agreeableness are more empowered. The relationship between agreeable and psychological empowerment was found to be mediated by affect-based trust and some of the intra-organizational relationship (i.e. leader-member exchange, and customer supportiveness). In other words, thanks to their trusting characteristics and their ability to develop and maintain relationship, agreeable service-workers tend to feel more empowered. Service workers high in openness to experience, as expected, was found to be more empowered since they had stronger notions of impact, self-determination, and competence. Additionally, extraversion was found to be significantly related to psychological empowerment’s dimensions of competence and meaning, and agreeableness was significantly associated with dimensions of meaning, self-determination, and competence. Finally, as expected agreeable service-workers were found to be empowered as they experience higher level of competence. Beside the theoretical contribution, assessing the relationship between a wide range of personality traits and psychological empowerment had a significant practical implication. By identifying empowerment-related personality traits, this study helps organizations to identify and select employees who can reach higher level of empowerment.